Wideband and Large Angle Electromagnetically Induced Transparency by the Equivalent Transmission Line in a Metasurface - Renxia Ning (Nature Portfolio, 2019)
Abstract A classical structure for a U-shaped metasurface exhibiting a wideband and large angle electromagnetically induced transparency (EIT) effect in the terahertz range is proposed. One horizontal and two vertical strips, which represent the bright and dark modes, respectively, are created for the U-shaped structure. The finite integration time domain (FITD) and equivalent circuit method are compared with the EIT result. The EIT effect is affected by the length of the vertical bar and by the distance from the vertical bar to the symmetry axis. The results show that the asymmetry of the main structure in the x and y axes makes it easier to achieve the EIT effect. In addition, by changing the incident angle, the EIT effect always exists until the angle of the incidental electromagnetic wave is 85 degrees. These results have many potential applications for terahertz filtering, large-angle switching and sensors.